Less Is More: Novel Hepatocyte-Targeted siRNA Conjugates for Treatment of Liver-Related Disorders - Adrien Weingärtner (Molecular Therapy: Nucleic Acids, 2020)
N-acetyl-galactosamine (GalNAc) conjugation enhances liver specificity for therapeutic oligonucleotides. Here we report on a novel design with improved activity and stability compared with a triantennary design. We applied a versatile monovalent serinol-GalNAc conjugation strategy. First, 1–4 serial serinol-linked GalNAc units were conjugated to terminal positions of small interfering RNA (siRNA) molecules. In primary hepatocytes, 5′ antisense GalNAc conjugates were inactive, whereas 3′ antisense and 3′ or 5′ sense conjugates displayed low activity for single GalNAc units, while 2–4 serial GalNAc conjugates were all equally potent. In mice, 5′ sense conjugates with 2–4 serial GalNAc units were all as potent as a triantennary GalNAc control (1 mg/kg). Second, increased spacing between two serial 5′ sense-conjugated GalNAc units did not affect in vitro activity. Finally, two single GalNAc units were positioned at opposite ends of the sense strand. A single dose (0.3 mg/kg) of this novel conjugate in mice showed a 3-fold reduction of serum target protein level at day 7 and 4-fold lower serum level at day 27, relative to an equimolar dose of a triantennary GalNAc conjugate of the same siRNA. Improved tritosome stability (by liquid chromatography-mass spectrometry [LC-MS] analysis) can at least partially explain the increased activity and duration of action for the novel GalNAc conjugate.